Розгляд проблеми забруднення атмосферного повітря через призму нової парадигми охорони здоров'я - Волкова, Юлія Володимирівна (My University, 2023)
Стаття присвячена висвітленню питання реалізації принципів медицини «4Р» у практичній діяльності фахівців з вивчення та аналізу впливу забрудненого атмосферного повітря на стан здоров’я населення. Так додержання принципу предиктивності дозволяє встановити не лише фактори ризику (пріоритетні забруднюючі речовини), а й групи ризику серед населення. Принцип профілактичності полягає у розробці системи заходів щодо мінімізації негативного впливу аєрополютантів на здоров’я, а відповідно збереження здоров’я як на індивідуальному, так і популяційному рівнях, й недопущення розвитку патології. The article is dedicated to elucidating the issue of implementation of the principles of "4R" medicine in the practical activities of specialists in the study and analysis of the influence of polluted atmospheric air on the state of the population's health. Thus, compliance with the principle of predictability makes it possible to establish not only risk factors (priority pollutants), but also risk groups among the population. The principle of prevention consists in the development of a system of measures to minimize the negative impact of air pollutants on health, and accordingly, the preservation of health both at the individual and population levels, and the prevention of the development of pathology. Personalization, that is, an individual approach to health control, consists in providing scientifically based recommendations, specific attitudes, first of all, in terms of lifestyle and preventive measures to prevent the development of diseases among patients. Participation is the involvement of the patient in active participation in the preservation and strengthening of his health. In order to implement this principle, experts must promptly provide reliable information about air quality, its pollution index, and risk levels for the development of pathology. After all, such information potentiates the active actions of the patient himself. Thus, the introduction of a new healthcare paradigm orients society to a wider introduction of preventive measures. And in this aspect, the analysis of the influence of the state of atmospheric air pollution on the state of health of the population is undeniably relevant.
Keywords: медицина 4Р; предиктивність; профілактичність; персоніфікованість; партисипативність; забруднення атмосферного повітря; medicine 4P; predictiveness; preventive action; personalization; participativeness; air pollution